ANALYSIS OF THE INTEGRATION OF LOCAL AND TARGET CULTURE IN EFL TEXTBOOK USED BY 11TH GRADERS IN SMA NEGERI 1 MAGELANG - Ratna Dwiyaning Raharjanti (Faculty of Education and Teachers Training, 2020)
Indonesia belongs to outer circle in Kachru’s classification (1985) where it places English as foreign language so Indonesian belongs to EFL (English as Foreign Language) learner. However, the students’ first and second language influence their way in learning English as their foreign language. Learning language cannot be separated from its culture, teaching a new language will inevitably include teaching a new culture. It is needed to know how far both target and local culture are integrated in the textbook entitled Bahasa Inggris for eleventh graders released by the Ministry of Education and Culture of Indonesia. Based on the writer’s observation, the eleventh graders of SMAN 1 Magelang still lack of knowledge about target culture mastery that is viewed from their way of speaking and writing. Therefore, the writer conducted a research by analyzing the textbook focused on the kinds of texts. The texts were analyzed by using Byram’s (1997) cultural content checklist to check whether they belonged to local or target culture. It is descriptive qualitative and uses documentation in collecting the data. The result shows that there are 12 of 14 texts (85.7%) that have dominant target culture and 2 texts (14.2%) that have dominant local culture. Therefore, it can be concluded that the textbook have reflected more dominant target culture. The writer suggested the EFL teachers should explain the target culture so that the students can reach intercultural communicative competence and also maintain the local culture.While for the Ministry of Education and Culture of Indonesia, it is better to give more specific sign of target culture so that the students can see the differences with the local culture.